Cover crops preceding the wheat crop - Skora Neto, Francisco; Campos, Antonio Carlos (Scientia Agraria Paranaensis, 2017)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> After harvesting of summer crops and before wheat planting, in the temperate region of southern Brazil, there is a time in which it could be possible grows short cycle cover crops. The objective was to evaluate some cover crop species during this period and its effect on wheat crop. The following treatments, in the years 2011 to 2013, were evaluated: fallow – bare soil (check), sunflower (Helianthus annuus L.), sunnhemp (Crotalaria juncea L.), forage radish (Raphanus sativus L.), pea forage (Pisum sativum L.) and buckwheat (Fagopyrum esculentum Moench). It was also evaluated the effect of time - 30, 15 and 0 days - between the formation of the mulching and the planting of wheat. In the average of the three years the highest wheat yield was obtained in sunflower mulch. The best wheat early development was observed in sunflower, radish forage and pea forage mulches. No effect of time after the formation of mulch on wheat yield was observed but there was a significant reduction in the number of emerged wheat plants in pea forage mulch when the wheat was seeded immediately after the mulch formation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>